EXPLOITATION OF THE ELDERLY IN THE FORM OF ONLINE BEGGING THROUGH SOCIAL MEDIA TIKTOK: EKSPLOITASI LANSIA DALAM BENTUK PENGEMISAN ONLINE MELALUI MEDIA SOSIAL TIKTOK - Nursita Fierdiana Dwi Andariesta; Astutik; Toetik Rahayuningsih (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Human exploitation is the act of exploiting that individuals or groups make of human beings, in order to obtain certain benefits. In the phenomenon that occurs, namely online begging, which is suspected of using the elderly as an object to benefit by committing inhumane actions, it has caused controversy and disrupted order in the community, especially the Tiktok social media. So it raises the problem of whether online begging by using the elderly as an object to gain profit through Tik Tok social media can be qualified as a criminal act of exploitation, This needs to be studied because there are no special rules regarding the exploitation of the elderly in the form of online begging. This research is a normative legal research by applying two approaches, namely statue approach and conceptual approach. The conclusion is, ILO (International Labour Organization) said the informal economic sector such as begging is a problem that often arises in many countries. Begging is a method/mode / form used by the perpetrator in seeking material and immaterial benefits in the act of exploitation. Based on this, according to Article 1 Number 7 of Law Number 21 of 2007 concerning the eradication of trafficking in Persons, online begging by using the elderly as an object for profit can be qualified as a crime of exploitation.